Pedagogical and psychological foundations of the development of artistic and creative abilities of students in the practice of decorative and applied art - Xaytmetov Dilshodjon To‘raevich (Genius Journals, 2023)
To put into practice the methods of active learning in higher educational institutions, allowing to achieve positive results in the development of artistic and creative abilities of students, as well as to carry out significant work on the development of art education using world experience.
Keywords: Technology; art education; art; ability